2005
DOI: 10.4049/jimmunol.175.3.1389
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Role of Macrophage Inflammatory Protein-3α Induction during Maturation of Intestinal Macrophages

Abstract: Intestinal macrophages (IMAC) are a central component in the defense of the intestinal mucosa against luminal microbes. In normal mucosa, monocytes differentiate to immunologically tolerant IMAC with a typical phenotype lacking activation markers such as CD14 and TLRs 2 and 4. CD33+ IMAC were isolated from normal intestinal mucosa by immunomagnetic beads. A subtractive hybridization subtracting mRNA from normal IMAC from those of in vitro differentiated macrophages was performed. IMAC differentiation was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Increased MIP-3α protein secretion was confirmed by ELISA. In vivo, MIP-3α protein expression in human intestinal epithelial cells and IMACs was determined in a nonquantitative manner by immunohistochemistry and flow cytometry [31]. In this work, we could confirmMIP-3α mRNA expression ex vivo in freshly isolated intestinal epithelial cells and IMACs.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Increased MIP-3α protein secretion was confirmed by ELISA. In vivo, MIP-3α protein expression in human intestinal epithelial cells and IMACs was determined in a nonquantitative manner by immunohistochemistry and flow cytometry [31]. In this work, we could confirmMIP-3α mRNA expression ex vivo in freshly isolated intestinal epithelial cells and IMACs.…”
Section: Discussionsupporting
confidence: 70%
“…Other cell types, such as endothelial cells, fibroblasts, and monocytes are also known to express MIP-3α [28,30]. High MIP-3α mRNA and protein expression are induced during the specific differentiation of IMACs as shown in previous studies from our laboratory [31]. Similarly, MIP-3α mRNA was found to be highly expressed in differentiated macrophages in the lung [28].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Under inflammatory conditions, epithelial cells [31], endothelial cells, fibroblasts, and monocytes are thought to be important sources of CCL20 production [16,32]. Similarly, some studies have shown that high expression of CCL20 is induced in differentiated macrophages in intestinal epithelium [33] and lung [32]. In human inflamed pulp sections, CCL20 is mostly expressed by macrophages accumulated in the area adjacent to carious lesions and CCR6 expression is also elevated in inflammatory infiltrating lymphocytes, which suggest that CCL20 may play a major role in the advancement of pulpal inflammation via the recruitment of CCR6-expressing lymphocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…In IBD this differentiation is altered at sites of inflammation [16,17,18,19,20,21,22,23]. A different phenotype with different functional properties occurs [16,17,18,19,20,21,22,23,24]. …”
Section: Tissue-specific Differentiation Of Innate Immune Cellsmentioning
confidence: 99%